Perforator Relocation in Free Style Local Perforator Flaps - Panse, Nikhil (World J Plast Surg, 2013)
Local perforator flaps have evolved over the time to provide complete and stable coverage of soft tissue defects. Technical advances and experience with the perforator flaps have allowed the harvest of local perforator flaps in a free style manner by offering greater freedom in flap selection. We have proposed a technical modification in the harvest of a perforator flap by relocating the perforator to an anatomically favorable location. This has led to decreased traction over the perforator and provided some amount of added length to the perforator.